PENGABDIAN RELIGIUS (BHAKTI) SEBAGAI RESPON TERHADAP MITOLOGI RAPAT PARA DEWA (DÉWA MAPASAMUHAN) DALAM KIDUNG WARGASARI - Sugiharta, I Putu Suweka Oka (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2025)
When the role of religion is confused by worldly elements, education cannot carry out its role properly. The aspirations of most humans are no longer to become human beings with noble character but to shift towards material orientations. Education was also affected and led to mercantilism. Many educational centers are then imaged as business centers rather than character building places. Religious devotion is a damper for the explosion of egoism in humans. In Hinduism religious service is called bhakti. This term is contained in many religious texts, including the Kidung Wargasari. The purpose of this research is to get an in-depth description of Religious Service Education (bhakti) in the Kidung Wargasari. The method used in this research is a qualitative method with content analysis in the text. The results of this study are that in the Kidung Wargasari there is self-devotion education (bhakti) such as devotion as educational worship, self-purification before praying, worship using offerings, belief in statues as manifestations of God, sincerity to serve God, apologies for all mistakes, worship with art, love for the environment, and religious unity